Competition policy and patent law under uncertainty regulating innovation - Manne, Geoffrey A.; Wright, Joshua D. (Cambridge University Press, 2011)
"The regulation of innovation and the optimal design of legal institutions in an environment of uncertainty are two of the most important policy challenges of the twenty-first century. Innovation is critical to economic growth. Regulatory design decisions, and, in particular, competition policy and intellectual property regimes, can have profound consequences for economic growth. However, remarkably little is known about the relationship between innovation, competition, and regulatory policy. Any legal regime must attempt to assess the tradeoffs associated with rules that will affect incentives to innovate, allocative efficiency, competition, and freedom of economic actors to commercialize the fruits of their innovative labors. The essays in this book approach this critical set of problems from an economic perspective, relying on the tools of microeconomics, quantitative analysis, and comparative institutional analysis to explore and begin to provide answers to the myriad challenges facing policymakers" -- Provided by publisher